IJCM_246A: Estimating the prevalence of seat belt usage in motor cars: A descriptive cross-sectional study in Mangalore - Jain Animesh; Rathi Priya; Gill Mnnat; Nirgudkar Isha; Hegde Apoorva; Gulati Yuvraj; Khatri Kaavya (Wolters Kluwer Medknow Publications, 2024)
Background: Every year 1.25 million people die of road traffic accidents. Several safety measures can be taken to prevent RTAs. The SDG 2030 set the target to halve the number of global death and injuries from road traffic accidents by the year 2020. The aim of this study is to estimate the prevalence of seat belt use and factors influencing it including driver characteristics, type of car and time of day and distractions while driving. Methodology: This Descriptive cross-sectional study was set on the major roads and intersections of Mangalore, recruiting the drivers and front-seat passengers in the motor cars at the time and site of observation. Results: A total of 6165 motor cars were observed. 15 (0.2%) of these cars had completely tinted car windows, therefore out of the total, 6150 motor cars could be properly observed. 70.91% (4361) of drivers were wearing seat belts. Seat belt usage among drivers was found to be higher on highways (76.6%) as compared to on residential and city roads (69.3%). In vicinity of traffic police, 76.5% of drivers were observed to be wearing seat belts in contrary only 67.8% of them were wearing seatbelts in the absence of traffic police. Prevalence of mobile phone use and other distractions amongst drivers was 2.1%. Out of 2646 adult front seat passengers observed, only 10.9% were wearing seat belts. Conclusion: Among drivers, type of motor car, traffic zone and type of road and presence of traffic police in vicinity are significantly associated factors with seatbelt usage. Among adult front seat passengers, type of motor car, traffic zone, type of road and presence of traffic police in vicinity are significantly associated. Among front seat child passengers, type of road and traffic zone are significantly associated with seat belt usage.